1978
DOI: 10.1111/j.1095-8649.1978.tb03416.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on effects of feeding level on growth and reproduction in haddock, Melanogrammus aeglefinus (L.) in captivity

Abstract: Individual haddock, Melanogrammus aeglefinus (L.) were maintained at different feeding levels in an aquarium from November until the completion of spawning. The mean duration of spawning was 33.2 days (range 19-59) during which an average of 16.6 (range 10-25) batches of eggs were produced. The size and dry weight of the eggs declined during the spawning period. Egg production and feeding level were correlated positively. There was some suggestion that when female haddock received low rations (< 5 kcal day-') … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 6 publications
11
125
0
3
Order By: Relevance
“…Considerable effort has been made in recent years to measure maternal factors affecting fecundity, egg size and fertilization success of gadoids that spawn freely in captivity (Hislop et al, 1978;Kjesbu et al, 1996;Thorsen et al, 2003). Paternal factors may have partly influenced the results of these experiments (especially related to fertilization).…”
Section: Paternal Effects On Reproductive Output In Paired Matingmentioning
confidence: 99%
“…Considerable effort has been made in recent years to measure maternal factors affecting fecundity, egg size and fertilization success of gadoids that spawn freely in captivity (Hislop et al, 1978;Kjesbu et al, 1996;Thorsen et al, 2003). Paternal factors may have partly influenced the results of these experiments (especially related to fertilization).…”
Section: Paternal Effects On Reproductive Output In Paired Matingmentioning
confidence: 99%
“…The supply of food to adult fish has a major impact on both their somatic growth as well as their gonad development (Wooton 1979). Hislop et al (1978) showed experimentally that haddock under reduced food supply not only have lower than normal fecundity, but also may fail to mature at all.…”
Section: Best Subset Regressionmentioning
confidence: 99%
“…Maternal physiological status, spawning experience (recruit or repeat spawners) or food rations during gametogenesis are all known to alter fecundity, egg and larval quality, as well as duration of the spawning season (Hislop et al, 1978;Kjesbu et al, 1991;Trippel, 1999;Marteinsdottir and Begg, 2002). Fecundity and relative fecundity generally increase with body size (Wootton, 1979;Kjesbu et al, 1998).…”
Section: Changes In Maturity In Response To Fishing Pressurementioning
confidence: 99%